An English dictionary for Muslim learners: is there a need? - Othman, Khairiah; Engku Ibrahim, Engku Haliza (2009)
This paper aims to highlight how meanings in English dictionaries differ from the meanings held by Muslims, hence, a need for teachers of English to highlight the differences when they teach English to Muslim learners. The presence of many English words and concepts, as conveyed through the English language, have meanings different from that which Muslims have ascribed to them has been highlighted by many Muslim scholars (al- Attas, 2001; al-Faruqi, 1986; Sa’Adeddin, 1996; Ratnawati, 1997; Abdussalam, 1999). Al- Faruqi (1986) for instance, advocates the use of Islamic English due to the fact that many English words do not convey, and unable to convey, the meanings that Muslims intend to convey. This is because many Arabic words are not translatable into English. Many of the meanings of Arabic words and phrases are of divine provenance and may not be separated from their Arabic forms. A study was conducted by 21 M.A students to find out how words in an English dictionary differ from the meanings held by Muslims. This paper has pedagogical implications for ESL teachers who teach English to Muslim learners.